Pembuatan Aplikasi Navigasi Pariwisata Provinsi Maluku Khususnya Kota Ambon Berbasis Android - Stien Tjiangdiono; Agustinus Noertjahyana; Leo Willyanto Santoso (Jurnal Infra, 2016)
Ambon city is a city that continues to develop new tourist attraction in a sustainable manner and has a lot of natural potential that can be used as a tourist attraction, especially nautical tourism, including underwater tourism potential, because areas with a large area of sea would save a million natural wealth. In addition to having the characteristics of marine tourism appeared as a hallmark of the city of Ambon island, also has a historical and cultural values are quite high. A form of historical and cultural heritage physique to date can be seen among them are the buildings of worship, places of burial, the houses of the king, the forms of sculpture associated with trust and heroism, monument struggle, forts and several lodging and adequate transportation.Features provided for tourism application is equipped with features such as information on attractions, events, hotels, culinary tours, transport and travel, shopping centers, in addition to the existing rating, comments and map navigation. Based on the results of testing this learning applications can run well on devices with the Android operating system version 4.1 to 5.1.1. In addition it is also testing done by giving questionnaires to 10 respondents to determine the level of satisfaction of respondents as much as 75%.